Ways to improve the diagnosis and treatment of interstitial lung disease associated with systemic sclerosis in the Siberian Federal District (materials of the advisory board of rheumatologists and pulmonologists from December 08, 2019) - L. I. Alekseeva; S. A. Terpigorev; E. V. Zonova; L. M. Kudelya; N. M. Babadaeva; A. V. Teteneva; A. A. Kondrashov; D. N. Orlov; T. V. Raskina; O. N. Anoshenkova; Yu. P. Chasovskikh; T. V. Kropotina; et al. (Бюллетень сибирской медицины, 2020)
The aim of the study was to develop ways to improve the diagnosis and treatment of systemic sclerosis (SSc)-ILD. Interstitial lung disease (ILD) is a common manifestation of SSc. In the territory of the Siberian Federal District (SFD), the number of patients with the progressive phenotype of SSc-ILD is approximately 750 people. When immunosuppressive therapy is ineffective and pulmonary fibrosis progresses, lung transplantation is indicated. The emergence of new possibilities of pathogenetic therapy currently requires studying the possibilities of their applications in real clinical practice on the territory of the SFD.Discussion. The results of a discussion of diagnostics, therapy, and routing of a rheumatology patient during the interdisciplinary observation of SSc-ILD in the SFD are presented. The reason for this discussion was the new data on the use of nintedanib in this category of patientsConclusion. To improve the efficiency of diagnosis and treatment of patients with SSc in the SFD, it is necessary to implement the principle of a multidisciplinary approach with the obligatory involvement of a pulmonologist and a radiologist (a specialist in CT diagnostics), and, if differential diagnosis is necessary in difficult clinical situations, of a pathomorphologist. An urgent task is the introduction of an algorithm for examining patients with SSc for the timely diagnosis of ILD in the territory of the Siberian Federal District. To improve the quality of medical care in the territory of the SFD for patients with ILD-SSc it is necessary to create a reference center in the city of Novosibirsk with the possibility of initiating anti-fibrosis therapy.